2020
DOI: 10.2478/hukin-2019-0105
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Age Effect in Professional Futsal Players

Abstract: The objective of this study was to verify the occurrence and effect size of relative age effect in professional futsal players, by observing how its presence and impact change according to the season, team level and player position. The sample was composed of 1873 professional futsal players who played in the First Division of the Spanish National Futsal League between seasons 2006-2007 and 2014-2015. The players’ birthdates were divided into quarters (Q1, Q2, Q3 and Q4). A relative age effect reversal was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 37 publications
1
23
0
3
Order By: Relevance
“…The lower prevalence of the RAE within futsal may be explained by the fact that futsal is less popular in Portugal than soccer, taking into account the broad differences in the number of registered players in both sports (according to 2019 data from registered male players, from the overall male Portugal population aged 5-19 years, 22% play soccer, while only 5% play futsal). Also, some players may have transitioned to futsal after a period in soccer where they did not excel, but they developed physical attributes, which may dilute the maturity disparities associated with chronological age differences (Lago-Fuentes et al, 2020). Also, as the official futsal laws of the game 4 allow unlimited changes of players during the match, less mature players might have more chances to develop technical and tactical skills, offsetting their physical disadvantages when compared with more mature peers.…”
Section: Discussionmentioning
confidence: 99%
“…The lower prevalence of the RAE within futsal may be explained by the fact that futsal is less popular in Portugal than soccer, taking into account the broad differences in the number of registered players in both sports (according to 2019 data from registered male players, from the overall male Portugal population aged 5-19 years, 22% play soccer, while only 5% play futsal). Also, some players may have transitioned to futsal after a period in soccer where they did not excel, but they developed physical attributes, which may dilute the maturity disparities associated with chronological age differences (Lago-Fuentes et al, 2020). Also, as the official futsal laws of the game 4 allow unlimited changes of players during the match, less mature players might have more chances to develop technical and tactical skills, offsetting their physical disadvantages when compared with more mature peers.…”
Section: Discussionmentioning
confidence: 99%
“…In team sports, individual performance is not achieved in the same way, but will largely depend on the playing position. For this reason, many studies made this distinction (Schorer et al, 2009b ; García et al, 2014 ; Ibañez et al, 2018 ; Yagüe et al, 2018 ; Lago-Fuentes et al, 2019 ; de la Rubia et al, 2020 ), concluding, generally, that relatively older players showed a better performance in those positions with greater physical and anthropometric requirements (i.e., pivots in basketball, backs in handball or midfielders in football), whereas in other playing positions, less conditioned by the biological and maturational development (i.e., shooting guard in basketball; wings in handball or forwards in football), there was no difference in competition performance depending on the relative age.…”
Section: Discussionmentioning
confidence: 99%
“…Es posible que las particularidades de cada deporte, y más específicamente de la muestra analizada, estén marcando diferencias en cómo se gestiona la ansiedad.. Así, el fútbol sala es un deporte menos popular que el fútbol, en consecuencia, es menos competitivo y está menos profesionalizado. El fútbol sala parece nutrirse de jugadores que vienen de jugar al fútbol (Lago-Fuentes, Rey, Padrón-Cabo, Prieto-Troncoso & Garcia-Núñez, 2020), por todo lo anterior el contexto del fútbol sala es mucho más diverso e incontrolable. Además, específicamente en nuestro estudio no se diferenció entre ansiedad cognitiva y somática, lo que podría dar lugar a diferentes conclusiones a las obtenidas.…”
Section: Discussionunclassified